Small molecule inhibitors target multiple neuropathological signaling to exert novel neuroprotection in intracranial aneurysms - Balkrishna, Acharya; Mishra, Shalini; Rana, Maneesha; Rajput, Satyendra Kumar; Pathak, Suhrud; Liu, Keyi; Dhanasekaran, Muralikrishnan; Arya, Vedpriya; Singh, Shalini (Frontiers in Pharmacology, 2024)
Intracranial aneurysms (IAs) represent a critical health concern due to their potential to rupture, leading to severe morbidity and mortality. Small molecule inhibitors (SMIs) have emerged as promising therapeutic candidates for managing IA progression and rupture risk. The current landscape of SMIs targets various molecular pathways implicated in IA pathogenesis, including inflammation, endothelial dysfunction, and extracellular matrix (ECM) degradation. Among the prominent therapeutic candidates discussed are statins, recognized for their multifaceted effects, anti-inflammatory properties, and enhancement of endothelial stability, which may mitigate IA progression. Matrix metalloproteinase inhibitors are also highlighted for their role in preserving ECM structural integrity, essential for preventing IA wall weakening and rupture. Furthermore, the review evaluates the efficacy of anti-inflammatory agents such as corticosteroids and cytokine inhibitors in attenuating IA growth driven by inflammatory processes. Our findings highlight the possibility of several pharmaceutical therapies that target matrix remodeling, inflammation, and other underlying processes to manage cerebral aneurysms. By precisely delivering therapeutic chemicals, such as antioxidants, gene therapy vectors, or anti-inflammatory medicines, to the aneurysm site, these SMI technologies treat the underlying pathophysiological causes while sparing healthy brain tissue. This review underscores the potential of SMIs as adjunctive or primary therapies in the comprehensive management of IAs, emphasizing the need for further clinical research to optimize their efficacy and safety in clinical practice.